Prescription of potentially inappropriate medication to older patients presenting to the emergency department: a nationally representative population study - Chang, Chirn-Bin (Sci Rep, 2018)
Potentially inappropriate medication (PIM) was associated with adverse clinical outcomes and higher healthcare resource utilization among older patients. In order to investigate the prevalence of PIM use based on three different sets of criteria and their associated factors among older patients in the emergency department (ED) in Taiwan. The National Health Insurance Research Database was used for this cross-sectional study. Older patients who visited the ED at least once in 2009 were enrolled. PIMs were identified based on the Beers Criteria, PIM-Taiwan criteria, and PRISCUS criteria. Average patient age was 76.7 ± 7.4 years and patients visited the ED 1.8 ± 2.1 times in 2009. The prevalence and frequency of being prescribed at least one PIM at each visit were high according to all three sets of criteria. Performance of the PIM-Taiwan criteria was only inferior to that of the Beers Criteria. The most important factor associated with PIM was the number of medications prescribed in the ED, and PIM use was associated with higher annual health resource utilization in the ED. PIM use was a significant issue and was associated with higher annual emergency care resource utilization in the ED.